Relation of Heart Rate and its Variability during Sleep with Age, Physical Activity, and Body Composition in Young Children - Herzig, David; Eser, Prisca; Radtke, Thomas; Wenger, Alina; Rusterholz, Thomas; Wilhelm, Matthias; Achermann, Peter; Arhab, Amar; Jenni, Oskar G.; Kakebeeke, Tanja H.; Leeger-Aschmann, Claudia S.; Messerli-Bürgy, Nadine; et al. (Frontiers in Physiology, 2017)
Background: Recent studies have claimed a positive association of physical activity and body composition on vagal tone. In pediatric populations, there is a pronounced decrease in heart rate with age. While this decrease is often interpreted as an age-related increase in vagal tone, there is some evidence that it may be related to a decrease in intrinsic heart rate. This factor has not been taken into account in most previous studies. The aim of the present study was to assess the effect of physical activity and body composition on heart rate variability independently of the decline in heart rate in young. Methods: Anthropometric measurements were taken in 309 children aged 2 to 6 years. Ambulatory electrocardiograms were collected over 14-18 hours comprising a full night and accelerometry over 7 days. Heart rate variability was determined of three different night segments: 1) over 5 min during deep sleep identified automatically based on heart rate variability characteristics; 2) during a 20 min segment starting 15 min after sleep onset; 3) over a 4-h segment between midnight and 4 a.m. Linear models were computed for anthropometric and physical activity variables with models adjusted for heart rate and other confounding variables (e.g. age for physical activity models). Results: We found a decline in heart rate with increasing physical activity and decreasing skinfold thickness. Heart rate variability parameters decreased with increasing age, height and weight in HR-adjusted regression models. These relationships were only found in segments of deep sleep detected automatically based on heart rate variability or manually 15 min after sleep onset, but not in the 4-h segment with random sleep phases. Conclusions: Contrary to most previous studies, we found no increase of standard heart rate variability parameters with age, however, when adjusted for heart rate, there was a significant decrease of heart rate variability parameters with increasing age. Without knowing intrinsic heart rate correct interpretation of heart rate variability in growing children is impossible.